Potential effectiveness of Vitrakvi (Larotrectinib) for treating types of solid tumors carrying NTRK genes and the impact of TRKC mutations - Ali Adel Dawood (La Granja: Revista de Ciencias de la Vida)
Vitrakvi is a cancer treatment that targets solid tumors with NTRK gene fusion. NTRKs are rare genetic effects that can arise in tumors from several organs, including the lungs, thyroid glands, and intestines. This study sought to identify the position at which Vitrakvi binds to tropomyosin receptor kinases (TRKs) as well as the effects of TRKC mutations on the fusion site. Materials and PubChem were used to obtain the chemical structure of Vitrakvi. The 3D structure of TRKs was derived from the PDB. Docking was implemented via AutoDock Vina. Docking, visualization, and sequence reconstruction were completed via the PyMol, BIOVIA, and PyRx programs. The fusion of Vitrakvi with TRKA and TRKB is altered if they are combined with their respective stimulators (BDGF and NT-4/5). TRKC combines with Vitrakvi in the same chain in which it is coupled to its stimulator (NT-3), but the fusion site shifts away from the triple mutation site. Even though clinical trials of TRK inhibitors have just started, there is reason to be hopeful for people with TRK mutations and the field of molecularly targeted medicines.